Tingginya Tingkat Stres dengan Kejadian Kekambuhan Gastritis pada Mahasiswa dalam Penyusunan Tugas Akhir di STIKes Bhakti Husada Mulia Madiun - Hanifah Ardiani (FORUM ILMIAH KESEHATAN, 2019)
Everyone can experience stress. Pressure, lifestyle and urgent life needs are things that can trigger stress on every individual. Stress has a negative effect through the neuroendrokrin mechanism on the digestive tract so it is at risk for gastritis. This study aims to determine the relationship of stress levels with the occurrence of gastritis recurrence. This research was a descriptive type, with cross sectional design. The population in this study were all students who were preparing their final project (218 students). The sampling technique in this study was purposive sampling. The sample size in this study was 76 respondents. Data were collected through filling out questionnaires. The statistical test used in this study was Chi-Square. The results showed that the p-value was 0.001 (